FILOSOFI HIDANGAN PADA PERAYAAN CHUNJIE DAN OSHOUGATSU : FILOSOFI HIDANGAN PADA PERAYAAN CHUNJIE DAN OSHOUGATSU - Rendy Aditya; Annisaa Nurul Atiqah; Desy Irmayanti (Universitas Negeri Surabaya, 2023)
Each country welcomes the joy of the turn of the year with its own traditions, including Chinese society and Japanese society. Chinese people welcome the New Year with the Lunar calendar, always serving a variety of dishes. Likewise, Japanese people welcome Oshougatsu according to the Gregorian calendar, always serving various types of food. These food dishes have a philosophical meaning that is believed to be passed down from generation to generation. China and Japan as neighbors have similarities in some of the dishes served at chunjie and oshougatsu celebrations. Based on this background, the focus of this study is to interpret each dish served at chunjie and oshougatsu celebrations. Then it is known; (1) the philosophy contained in each chunjie and oshougatsu celebration dish, (2) the similarities and differences between the chunjie and oshougatsu celebration dishes. The method used in this study is descriptive qualitative. Based on data sources from interviews with Chinese and Japanese people, it was found data in the form of the habit of eating special dishes at chunjie and oshougatsu celebrations. The data is used to compare the two cultures towards chunjie and oshougatsu dishes. Based on the data, it can be concluded that every dish at chunjie and oshougatsu celebrations has Japansea deep philosophy to interpret life in the future. The similarity of dishes enjoyed by the Chinese and Japanese people when celebrating the new year are (1) Fish, (2). Noodles. While the differences in foods that are not consumed by Japanese people when celebrating the new year are (1). Dumplings, (2). Pig’s feet, (3). Meatballs, (4). Chicken. Food that are not consumed by Chinese people are (1). Fish, (2). Herring roe pieces, (3) rolled seaweed, (4). Shrimp (5) egg rolls, (6). Soup.